Search for the decay Bs -> D*-+ π+- - collaboration, L; Aaij, R; Beteta, C; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; Ali, S; et al. (2013)
A search for the decay Bs -> D*-+ π+- is presented using a data sample corresponding to an integrated luminosity of 1.0 fb-1 of pp collisions collected by LHCb. This decay is expected to be mediated by a W-exchange diagram, with little contribution from rescattering processes, and therefore a measurement of the branching fraction will help to understand the mechanism behind related decays such as Bs -> π+ π- and Bs -> D Dbar. Systematic uncertainties are minimised by using B0 -> D*-+ π+- as a normalisation channel. We find no evidence for a signal, and set an upper limit on the branching fraction of BR(Bs -> D*-+ π+-) < 6.1 (7.8) x10^(-6) at 90% (95%) confidence level.